Calcium Phosphate Materials for Bone Repair Application - Li, Xiaoming; Huang, Jin; Fan, Yubo (Recent Patents on Biomedical Engineering (Discontinued), 2011)
Calcium phosphates, with a composition and structure similar to the mineral phase of bone, have been recognized as satisfactory materials for bone repair because of their excellent biocompatibility, osteoconductive, and bioactivity. In this paper, the recent related patents are reviewed, including four parts, such as calcium phosphate bioceramics, calcium phosphate coatings, calcium phosphate based particles and calcium phosphate with electromagnetic stimulation for bone repair, which might indicate that calcium phosphate materials have been widely used to repair bone. However, there are still some other interesting points, which are expected to be included in the coming patents, four points of which, such as the calcium phosphates with novel specific microstructures, composites that include calcium phosphates and carbon nanotubes, composites that include calcium phosphates and collagen and calcium phosphates based system that could be combined with many different drugs, are described in the conclusion and perspectives part.
Keywords: Calcium phosphate bioceramics